ASPECTS REGARDING THE STUDY OF HYDRAULIC AND MECHANICAL PARAMETERS OF A ”SPIDER CRANE” SYSTEM - NICUŞOR BAROIU; VIOREL PĂUNOIU; VIRGIL GABRIEL TEODOR; GEORGIANA-ALEXANDRA MOROŞANU; RĂZVAN SEBASTIAN CRĂCIUN (Journal of Engineering Studies and Research)
Recognizing the crucial role that transport and lifting installations play in various sectors, including industry, construction, and extraction, as well as in mechanizing loading and unloading operations, and the movement of equipment or materials, special attention must be oriented to the diversification and the production of these installations by using the most advanced technologies. The paper presents some operating principles and characteristics of a lifting and transport Spider Crane installation equipment. This installation is considered a more economical and efficient alternative to traditional cranes for works where lifting requirements are below certain limits and significant height. Thus, an analysis of the hydraulic lifting system was carried out, based on the calculation of hydraulic fluid flows for the drive pumps. Also, was evaluated the specific speeds and forces of the hydraulic cylinders, a mechanical analysis of the clamping system with hook, as well as a finite element analysis of some mechanical and hydraulic components.